Kinetics of Red-Pigment Fermentation by Monascus Purpureus FTC 5391 in Shake Flask Culture and Stirred Tank Fermenter Using Different Carbon and Nitrogen Sources - Abdul Manan, Musaalbakri (2005)
A newly isolated red-pigment producing fungus from local source was identified using Microbial Identification System based on fatty acids profiles. Growth morphology and structure of the fungus were also identified using Scanning Electron Microscope. Monospore isolation technique was performed to obtain the improved strain that has high and consistent ability to produce red pigment. Kinetics of red-pigment fermentation by this local strain, identified as Monascus purpureus FTC 5391, in 500 mL shake flask culture and 2 L stirred tank fermenter using different carbon and nitrogen sources were also investigated.